Neottia nyinyikyawii (Orchidaceae: Epidendroideae), a new species from Chin State, Myanmar - Mu, Aye-Thin; Aung, Mung-Htoi; Jin, Xiao-Hua (Phytotaxa, 2020)
Neottia nyinyikyawii, a new species of Orchidaceae, is described and illustrated from Nat Ma Taung, Chin State, Myanmar. Neottia nyinyikyawii is morphologically similar to N. chandrae and N. tenuis, but differs from them by having leaves borne in the middle of the plant, elliptic lip 7.0–8.0 × 1.5–2.0 mm and falcate lobelets. A preliminary assessment of the risk of extinction of this new species is Least Concern (LC).